Estimasi Nilai Ekonomi Dan Willingness to Pay (WTP) Masyarakat Terhadap Upaya Pelestarian Sumberdaya Air Di Desa Sukadamai, Kecamatan Dramaga, Bogor, Jawa Barat - Irfan Gunawan Matondang; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
This study aims to estimate the value of the community's Willingness to Pay (WTP) towards the preservation of water resources in Sukadamai Village and to estimate the economic value of water resources in Sukadamai Village, Dramaga District, Bogor, West Java. This research was conducted in February to March 2020, using primary and secondary data with random sampling methods and the respondents as many as 30 people. Analysis of the data used is quantitatively using the Contingent Valuation Method (CVM). Contingent Valuation Method is a method of gathering information about people’s preference or willingness to pay with direct questioning techniques. The results showed that the water resources in Sukadamai Village has several problems in the payment of fees and waste problems. The analysis also shows that of the 15 respondents, there were 5 respondents who were willing to pay more with an average Willingness to Pay of Rp 11,667 / KK / month using non-parametric calculations of Turnbull and K-M-T techniques. The estimation of the economic value of the water resources in Sukadamai is Rp. 28,747,488. The results of the analysis show that public awareness about the importance of the water resources existence in Sukadamai Village is still very low. Key word: contingent valuation method, economy, water resource, willingness to pay